2013
DOI: 10.17221/33/2013-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Application and limitations of growth models for silvicultural purposes in heterogeneously structured forest in Sweden

Abstract: ABSTRACT:The paper addresses the problem of estimating future stand development in heterogeneously structured forests in Sweden; specifically, multi-layered spruce stands and mature pine stands with advanced spruce undergrowth. We first introduce various supporting concepts and models with their empirical databases, model validation and constraints. Secondly, Swedish single-tree growth functions designed for more heterogeneously structured forest are tested using data from inventory plots, a thinning experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In tests on NFI data and long-term research plot data, the Heureka growth models have been shown to be quite reliable for even-aged management given there are no catastrophic events such as fire or storm [40]. They have performed less accurately in tests on heterogeneously structured forest [72], for which growth in long-term projections also depends on the natural ingrowth of trees [41]. The growth models have also been shown to be reasonably accurate for projecting growth of non-managed old growth forests [73].…”
Section: Discussionmentioning
confidence: 99%
“…In tests on NFI data and long-term research plot data, the Heureka growth models have been shown to be quite reliable for even-aged management given there are no catastrophic events such as fire or storm [40]. They have performed less accurately in tests on heterogeneously structured forest [72], for which growth in long-term projections also depends on the natural ingrowth of trees [41]. The growth models have also been shown to be reasonably accurate for projecting growth of non-managed old growth forests [73].…”
Section: Discussionmentioning
confidence: 99%
“…Aiming at the transformation to a spruce-dominated single-tree selection forest, more attention should be paid to tree species with vital growth under varying levels of canopy closure. Given our findings and current management conditions in the study region, Norway spruce, European beech and sessile oak appear to be the most suitable species in this regard [26,68]. To balance removal and ingrowth of trees over time, both gaps to initiate or release regeneration and closed canopy sections without regeneration are necessary, as this will assure the continuous supply of regeneration and mature, harvestable trees.…”
Section: Discussionmentioning
confidence: 76%
“…The paucity of data from long-term experiments in mixed forests highlights a need for modeling efforts, but experiments will also be needed to validate and develop such models [45]. Therefore, two important conclusions are (1) to maintain the existing experiments for future validation and development of management-related growth models, and (2) to complement the limited number of experiments with new study approaches (e.g., [25,26]).…”
Section: The Mixing Effect Of Observed Increment Without Spruce Growtmentioning
confidence: 99%